Potencial antiproliferativo, antigenotóxico e análise fitoquímica dos extratos aquosos e do óleo de Baccharis dracunculifolia DC. (Asteraceae) - Pasqualli, Marina (2016)
Baccharis dracunculifolia is a medicinal species, popularly known as broom, and has its use based on the preparation of infusions of leaves for the treatment of gastric disorders, physical fatigue, lack of appetite, fever diseases and organic weakness. Its essential oil stands out in the perfumery industry as well as in biological studies. The study aimed to evaluate the potential antiproliferative, genotoxic and antigenotoxic of two populations of B. dracunculifolia on the test systems Allium cepa L. and Lactuca sativa L. as well as performs the phytochemical analysis of the aqueous extract and oil obtained from the leaves. The material used in the preparation of infusions and oil consisted of two populations collected in Santa Maria (SM) and São Pedro do Sul (SPS), which part was dehydrated to prepare infusions in 5g.L-1 and 10g.L -1 concentrations, and the other part was frozen for later extraction of essential oil. To determine the antiproliferative, genotoxic and antigenotoxic activities, the effects of aqueous extracts and oil on the A. cepa test and L. sativa systems. The experiment whith A. cepa consisted of twelve groups of four bulbs, each group corresponding to a treatment. The bulbs were rooted in water an than subjected to treatments for 24 hours. The experiment whith L. sativa consisted of nine groups of four Petri dishes. Each plate was soacked whith about 7 mL of extract, which were in contact with the seeds for 72 hours. After this period the roots of A. cepa and L. sativa seeds were collected, fixed in Carnoy 3:1 and stored in refrigerated in 70% ethanol until the preparation of the slides. The determination of phenolic compounds from aqueous extracts was performed by the High Performance Liquid Chromatography (HPLC). The compounds of the essential oil were determined by Gas Chromatography (GC). The genotoxicity data were subjected to analysis Chi-square test, whereas the data of the chromatographic analysis were subjected to Tukey test (p <0.05). The results of the A. cepa test showed that extracts from B. dracunculifolia have antiproliferative and antigenotoxic potential as well as the essential oil of the SPS population, while the oil SM population induces cell proliferation. For L. sativa test, aqueous extracts of the two populations demonstrated atiproliferativo effect, except the aqueous extract of SPS population at a concentration of 10 g.L-1, in which there was an increase in cell proliferation. Chromatographic analysis indicated as major compounds, p-coumaric acid to the aqueous extracts and E-nerolidol to the essential oil.